Flow battery composite membrane-electrode, preparation method thereof and flow battery
By designing a composite membrane-electrode of the flow cell with a proton exchange membrane and a carbon nanofiber layer, the problem of the flow frame affecting power density and contact resistance in the flow cell stack is solved, and a higher stack power density and energy conversion efficiency are achieved.
Patent Information
- Application Number
- CN202311408573.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2025-04-29
AI Technical Summary
The existing liquid flow battery stack affects the power density due to the volume and mass of the liquid flow frame, and it is difficult to avoid a large contact resistance between the electrode-film, electrode-bipolar plate, which reduces the energy conversion efficiency.
A liquid flow battery composite membrane-electrode is designed, including a proton exchange membrane coated with a catalytic coating and two liquid diffusion layers. The proton exchange membrane has a main body part and multiple synaptic part structures. The liquid diffusion layer is a carbon nanofiber layer. The liquid diffusion layer is bonded to the proton exchange membrane through a hot pressing process.
It effectively increases the reaction area of the electrode, improves the catalytic efficiency, reduces the contact resistance between materials, reduces the stack volume and mass, and improves the power density of the liquid flow battery stack.
Smart Images

Figure CN119905620A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of liquid flow batteries, and in particular relates to a liquid flow battery composite membrane-electrode and a preparation method thereof, and a liquid flow battery. Background Art
[0002] In order to solve the problems of peak-shifting waste and unsustainable utilization of many clean energy sources, the development of green and new energy storage methods has become an important area of concern for researchers. As a type of energy storage technology, flow batteries have the advantages of fast response speed, high safety, independent power and capacity, deep discharge, high efficiency and environmental friendliness. It has gradually become the energy storage technology with the most development potential.
[0003] The standard open circuit voltage of a single cell of a flow battery is relatively small. To meet practical applications, a certain number of single cells need to be assembled in series into a stack in order to obtain the required voltage. At present, the stack of flow batteries mostly adopts the structure of bipolar plate-flow frame-electrode-diaphragm-electrode-flow frame-bipolar plate. The electrode itself does not participate in the redox reaction, but the reaction of the stack is closely related to the intrinsic properties of the electrode material and is largely limited to the electrode reaction area hollow in the flow frame. The flow frame can effectively improve the uniformity of the electrolyte flowing through the electrode surface, but its volume and mass will seriously affect the power density of the stack. The stack of flow batteries is usually assembled by pressing and stacking. The contact resistance between the components depends on the pressure applied to the outside of the stack. It is inevitable that a large contact resistance will be generated between the electrode-membrane and the electrode-bipolar plate, reducing the energy conversion efficiency of the stack. Summary of the invention
[0004] In order to solve the above problems existing in the prior art, the present invention provides a flow battery composite membrane-electrode and a preparation method thereof, and a flow battery. The technical problem to be solved by the present invention is achieved by the following technical solutions:
[0005] The present invention provides a composite membrane-electrode for a flow battery, comprising: a proton exchange membrane with a catalytic coating on the surface and two liquid diffusion layers, wherein:
[0006] The proton exchange membrane comprises a Nafion membrane, and the proton exchange membrane comprises a main body and a plurality of synapse parts located on both sides of the main body;
[0007] The multiple synaptic portions on each side are arranged in a parallel and equally spaced one-dimensional array along the main body, and the multiple synaptic portions on both sides are symmetrically arranged about the main body;
[0008] The two liquid diffusion layers are correspondingly attached to a plurality of synapse portions on both sides of the proton exchange membrane.
[0009] In one embodiment of the present invention, the catalytic coating is a carbon nanotube catalytic coating with a catalyst loaded therein, and the catalyst is a metal-based catalyst, a metal oxide catalyst or a carbon-based electrocatalyst.
[0010] In one embodiment of the present invention, a distance between an end of the synapse portion away from the main body portion and the main body portion is 0.1 μm to 100 μm.
[0011] In one embodiment of the present invention, the distance between adjacent synaptic portions is greater than 0.1 μm.
[0012] In one embodiment of the present invention, the liquid diffusion layer comprises a carbon nanofiber layer.
[0013] The present invention provides a method for preparing a composite membrane-electrode for a flow battery, comprising:
[0014] Step 1: Pour the Nafion solution into a template having a one-dimensional array structure, and evaporate the solvent to obtain a Nafion array membrane;
[0015] Step 2: placing a strip Nafion membrane on a template having a Nafion array membrane, fusing the strip Nafion membrane with the Nafion array membrane by a hot pressing process, and obtaining a proton exchange membrane after demolding, wherein the strip Nafion membrane is located in the middle of the Nafion array membrane, so that the Nafion array membrane forms a plurality of synaptic portions on both sides of the strip Nafion membrane;
[0016] Step 3: preparing a carbon nanotube material with a catalyst inside, and preparing a catalytic coating slurry using the carbon nanotube material with a catalyst inside;
[0017] Step 4: spraying the catalytic coating slurry onto the entire surface of the proton exchange membrane to obtain a proton exchange membrane with a catalytic coating on the surface;
[0018] Step 5: Prepare a liquid diffusion layer using carbon nanofibers;
[0019] Step 6: Use a hot pressing process to bond two liquid diffusion layers to the multiple synapse parts on both sides of the proton exchange membrane to obtain a liquid flow battery composite membrane-electrode.
[0020] In one embodiment of the present invention, step 3 comprises:
[0021] Step 3.1: Synthesizing carbon nanotube materials with catalysts loaded inside by wet impregnation method;
[0022] Step 3.2: mixing the carbon nanotube material carrying the catalyst inside and the carbon nanofiber according to a certain proportion, wherein the mass fraction of the carbon nanotube material carrying the catalyst inside is 1 to 100 wt %, and the mass fraction of the carbon nanofiber is 0 to 99 wt %;
[0023] Step 3.3: Disperse the mixture into a mixed solution of propanol and water containing Nafion solution, wherein the mass fraction of the Nafion solution is 1% to 10%, and the volume ratio of propanol to water is 1:1, and perform ultrasonic treatment on the mixed solution to form a uniformly dispersed suspension as a catalytic coating slurry.
[0024] In one embodiment of the present invention, step 5 comprises:
[0025] Step 5.1: adding carbon nanofibers to a sodium dodecyl sulfate aqueous solvent containing a dispersant, and performing ultrasonic dispersion to obtain a uniformly dispersed suspension; wherein the mass ratio of the carbon nanofibers to the dispersant is 1:2;
[0026] Step 5.2: After filtering and forming the suspension in step 5.1, remove the dispersant to obtain a carbon nanofiber layer as a liquid diffusion layer.
[0027] In one embodiment of the present invention, in step 2 and step 6, the process parameters of the hot pressing process are: the hot pressing temperature is 120° C. to 170° C., and the hot pressing pressure is 1 to 10 MPa.
[0028] The present invention provides a liquid flow battery, comprising the liquid flow battery composite membrane-electrode as described in any one of the above embodiments.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The composite membrane-electrode of the liquid flow battery of the present invention, the proton exchange membrane comprises a main body and a plurality of synapse parts located on both sides of the main body, and a carbon nanotube catalytic coating with a catalyst inside is coated on the surface of the proton exchange membrane. The structure of the proton exchange membrane is utilized to effectively increase the reaction area of the electrode, while avoiding the attenuation of catalytic efficiency caused by catalyst agglomeration during the reaction.
[0031] 2. In the composite membrane-electrode of the flow battery of the present invention, the liquid diffusion layer is a carbon nanofiber layer, which has a large porosity, and can further improve the catalytic efficiency of the electrode while increasing the specific surface area of the membrane-electrode.
[0032] 3. The composite membrane-electrode of the flow battery of the present invention integrates the proton exchange membrane and the electrode to form a flow battery membrane-electrode. When it is applied to the flow battery stack, the flow frame components in the traditional flow battery stack can be removed, and the electrolyte distribution uniformity provided by the flow frame can be ensured by adding flow channels on the bipolar plates. The structure of the flow battery stack can effectively reduce the contact resistance between the materials, while reducing the volume and mass of the stack, and improving the overall power density of the flow battery stack.
[0033] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the following specifically cites a preferred embodiment and describes it in detail with the accompanying drawings as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the structure of a composite membrane-electrode of a flow battery provided by an embodiment of the present invention;
[0035] Figure 2 It is a flow chart of a method for preparing a composite membrane-electrode for a flow battery provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0036] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, a liquid flow battery composite membrane-electrode and its preparation method, and a liquid flow battery proposed in accordance with the present invention are described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0037] The above and other technical contents, features and effects of the present invention are clearly presented in the following detailed description of the specific implementation modes in conjunction with the accompanying drawings. Through the description of the specific implementation modes, the technical means and effects adopted by the present invention to achieve the predetermined purpose can be more deeply and specifically understood. However, the attached drawings are only for reference and explanation purposes and are not used to limit the technical solutions of the present invention.
[0038] In the first aspect, the present invention provides a composite membrane-electrode for a flow battery, see Figure 1 , Figure 1 is a schematic diagram of the structure of a composite membrane-electrode of a flow battery provided by an embodiment of the present invention, such as Figure 1 As shown, the composite membrane-electrode of the flow battery of this embodiment includes a proton exchange membrane 1 with a catalytic coating 2 coated on the surface and two liquid diffusion layers 3.
[0039] In an optional embodiment, the proton exchange membrane 1 may be a Nafion membrane.
[0040] Optionally, the proton exchange membrane 1 includes a main body 11 and a plurality of synapse parts 12 located on both sides of the main body; the plurality of synapse parts 12 on each side are arranged in a parallel and equally spaced one-dimensional array along the main body 11 , and the plurality of synapse parts 12 on both sides are symmetrically arranged about the main body 11 .
[0041] It should be noted that Figure 1 The shape of the synapse portion 12 shown is only an example. Optionally, the shape of the synapse portion 12 may be other shapes such as conical, cylindrical, spherical, etc.
[0042] In this embodiment, the synapse portion 12 can effectively increase the specific surface area and improve the battery performance. Therefore, the smaller the spacing, the more the number of unit synapse portions 12, and the larger the specific surface area. The larger the length dimension of the unit synapse portion 12, the larger the corresponding specific surface area, but the increase in the length dimension will be accompanied by the collapse of the synapse portion 12 and the occurrence of the end absorption phenomenon between adjacent synapse portions 12, thereby destroying the orderliness of the arrangement of the proton transmission channel and the reduction of the reaction specific surface area. Optionally, the distance between the end of the synapse portion 12 away from the main body 11 and the main body 11 is 0.1μm to 100μm. The spacing between adjacent synapse portions 12 is greater than 0.1μm.
[0043] In an optional embodiment, the catalytic coating is a carbon nanotube catalytic coating with a catalyst loaded therein.
[0044] Optionally, the catalyst is a metal-based catalyst, a metal oxide catalyst or a carbon-based electrocatalyst, for example, Bi, Ir, Ru, Rh, Pt, Pd, Cu, Au, CeO2, TiO2, NbO5, WO3, Mn3O4 and the like.
[0045] In an optional embodiment, the two liquid diffusion layers 3 are correspondingly attached to the multiple synapse portions 12 on both sides of the proton exchange membrane 1 .
[0046] Optionally, the liquid diffusion layer 3 can be a carbon nanofiber layer. Since the carbon nanofiber layer has a high porosity, a large number of reaction medium transmission channels can be formed, so that the electrolyte and the catalyst layer are fully in contact, the catalytic efficiency is improved, and the electrolyte utilization rate is improved. In addition, carbon nanofibers also have excellent conductivity. As an electron transmission path, they can reduce the polarization and ohmic polarization of the electrodes in the battery and improve the battery performance. The carbon nanofiber layer has high tensile strength, high tensile modulus and high flexibility, which is conducive to improving the mechanical properties of the membrane electrode.
[0047] It is worth noting that the liquid diffusion layer 3 and the proton exchange membrane 1 are tightly fitted together by heat pressing. In order to see the structure of each part clearly, Figure 1 There is no stacking between the two in the structural diagram.
[0048] The structure of the composite membrane-electrode of the flow battery of this embodiment can, on the one hand, provide a large number of orderly proton transmission channels, improve the proton conductivity of the membrane electrode, and enable the battery stack to obtain a higher voltage efficiency and improve the energy efficiency of the battery. On the other hand, it can effectively increase the reaction surface area of the membrane electrode. The increase in the specific surface area of the membrane electrode can effectively improve the power density of the battery.
[0049] In addition, in this embodiment, the catalyst is loaded inside the carbon nanotubes, which can make the catalyst have a smaller particle size and good dispersibility, because the nano space inside the carbon nanotubes can effectively inhibit the agglomeration of the catalyst, inhibit the failure of the catalytic activity, and improve the stability. Therefore, using carbon nanotubes to load the catalyst can reduce the loading amount of the catalyst, achieve the improvement of battery performance and effective control of cost.
[0050] In a second aspect, an embodiment of the present invention provides a method for preparing a composite membrane-electrode for a flow battery, see Figure 2 , Figure 2 is a flow chart of a method for preparing a composite membrane-electrode for a flow battery provided by an embodiment of the present invention, such as Figure 2 As shown, the preparation method of the composite membrane-electrode of the flow battery of this embodiment comprises:
[0051] Step 1: Pour the Nafion solution into a template having a one-dimensional array structure, and evaporate the solvent to obtain a Nafion array membrane;
[0052] Step 2: placing a strip Nafion membrane on a template having a Nafion array membrane, fusing the strip Nafion membrane with the Nafion array membrane by a hot pressing process, and obtaining a proton exchange membrane after demolding;
[0053] In an optional embodiment, the process parameters of the hot pressing process in step 2 are: the hot pressing temperature is 120° C. to 170° C., and the hot pressing pressure is 1 to 10 MPa. For example, the hot pressing temperature may be 140° C., and the hot pressing pressure may be 5 MPa.
[0054] In an optional embodiment, the entire mold can be transferred to a water tank filled with ethanol aqueous solution and demolded to obtain a Nafion proton exchange membrane with a Nafion array.
[0055] In this embodiment, the strip-shaped Nafion membrane is located in the middle of the Nafion array membrane, so that the Nafion array membrane forms a plurality of synapse portions on both sides of the strip-shaped Nafion membrane.
[0056] Optionally, the distance between the end of the synaptic part away from the strip Nafion membrane and the strip Nafion membrane is 0.1 μm to 100 μm. The spacing between adjacent synaptic parts, that is, the spacing between adjacent units in the one-dimensional array arrangement structure in the template is greater than 0.1 μm.
[0057] Alternatively, the strip Nafion membrane may be a commercial Nafion membrane currently on the market.
[0058] It should be noted that there is no limit to the overall area (length*width) of the one-dimensional array arrangement structure, and the size of the mold can be adjusted according to the required film size to achieve regulation of the array area.
[0059] Step 3: preparing a carbon nanotube material with a catalyst inside, and preparing a catalytic coating slurry using the carbon nanotube material with a catalyst inside;
[0060] Optionally, the catalyst is a metal-based catalyst, a metal oxide catalyst or a carbon-based electrocatalyst, for example, Bi, Ir, Ru, Rh, Pt, Pd, Cu, Au, CeO2, TiO2, NbO5, WO3, Mn3O4 and the like.
[0061] In an optional embodiment, step 3 includes:
[0062] Step 3.1: Synthesizing carbon nanotube materials with catalysts loaded inside by wet impregnation method;
[0063] By way of example, the preparation process of the carbon nanotube material (Pt / CNTs) loaded with a Pt base is described by taking a platinum (Pt) base as an example.
[0064] First, carbon nanotubes (CNTs) were treated by HNO3 reflux at 125°C for 6 hours. Optionally, the length of CNTs was 0.1-50 μm and the diameter was 1-100 nm. 100 mg of the treated CNTs were taken out and immersed in 0.3 ml H2PtCl6 ethanol solution at room temperature, and then 0.2 ml H2O was added. After being completely dried, they were treated in H2 atmosphere at 200°C for 3 hours to obtain Pt / CNTs.
[0065] Step 3.2: mixing the carbon nanotube material carrying the catalyst inside and the carbon nanofiber according to a certain proportion, wherein the mass fraction of the carbon nanotube material carrying the catalyst inside is 1 to 100 wt %, and the mass fraction of the carbon nanofiber is 0 to 99 wt %;
[0066] Optionally, the carbon nanofibers (CNFs) have a length of 1 to 1000 μm and a diameter of 10 to 1000 nm.
[0067] In this embodiment, CNFs with a larger diameter are cross-entangled with each other to form a film with good electrochemical properties and excellent mechanical properties by wrapping and winding a carbon nanotube material with a smaller diameter and carrying a catalyst, such as Pt / CNTs, without the need for additional adhesives. Due to the close entanglement between CNFs and Pt / CNTs, a dense conductive network structure is formed, providing high conductivity, while significantly reducing the agglomeration phenomenon that may occur in CNTs loaded with Pt during the electrochemical reaction, effectively improving the catalytic activity and catalytic life of the catalyst.
[0068] Step 3.3: Disperse the mixture into a mixed solution of propanol and water containing Nafion solution, wherein the mass fraction of the Nafion solution is 1% to 10%, and the volume ratio of propanol to water is 1:1, and perform ultrasonic treatment on the mixed solution to form a uniformly dispersed suspension as a catalytic coating slurry.
[0069] Step 4: spraying the catalytic coating slurry onto the entire surface of the proton exchange membrane to obtain a proton exchange membrane with the catalytic coating coated on the surface;
[0070] Optionally, the prepared Nafion proton exchange membrane is placed on an adsorption platform, and the catalytic coating slurry is evenly sprayed onto both sides of the proton exchange membrane by ultrasonic spraying technology.
[0071] Step 5: Prepare a liquid diffusion layer using carbon nanofibers;
[0072] In an optional embodiment, step 5 includes:
[0073] Step 5.1: adding carbon nanofibers to a sodium dodecyl sulfate aqueous solvent containing a dispersant, and performing ultrasonic dispersion to obtain a uniformly dispersed suspension; wherein the mass ratio of carbon nanofibers to the dispersant is 1:2;
[0074] Optionally, ultrasonic dispersion is performed for 2 hours to obtain a uniformly dispersed suspension.
[0075] Optionally, the dispersant may be other anionic dispersants, nonionic dispersants or polymer dispersants, such as polyethylene glycol, sodium dodecyl sulfate, Triton X100, etc.
[0076] Step 5.2: After filtering and forming the suspension in step 5.1, remove the dispersant to obtain a carbon nanofiber layer as a liquid diffusion layer.
[0077] Optionally, after the suspension is filtered and formed, it is treated at 350° C. for 1 hour to remove residual dispersant.
[0078] Step 6: Use a hot pressing process to fit the two liquid diffusion layers to the multiple synaptic parts on both sides of the proton exchange membrane to obtain a liquid flow battery composite membrane-electrode.
[0079] In an optional embodiment, the process parameters of the hot pressing process in step 6 are: the hot pressing temperature is 120° C. to 170° C., and the hot pressing pressure is 1 to 10 MPa. For example, the hot pressing temperature may be 140° C., and the hot pressing pressure may be 5 MPa.
[0080] For the specific contents of the preparation method of the liquid flow battery composite membrane-electrode and the corresponding beneficial effects, please refer to the relevant contents of the liquid flow battery composite membrane-electrode provided in the first aspect, which will not be repeated here.
[0081] In a third aspect, an embodiment of the present invention provides a liquid flow battery, comprising a liquid flow battery composite membrane-electrode as described in the first aspect. When the liquid flow battery composite membrane-electrode is applied to a liquid flow battery stack, the liquid flow frame component in the traditional liquid flow battery stack can be removed, and the electrolyte distribution uniformity provided by the liquid flow frame can be ensured by adding flow channels on the bipolar plates.
[0082] The specific working process is as follows: the electrolyte flows through the surface of the liquid diffusion layer, first contacts the liquid diffusion layer and starts the redox reaction. Since the concentration of V ions in the electrolyte is high at this time, no catalyst is needed for catalysis. At the same time, it diffuses to the catalytic coating through the reaction medium transmission channel (carbon nanofiber pores). The electrolyte reaches the catalytic coating. At this time, the concentration of V ions in the electrolyte is low, but the redox reaction rate is accelerated under the synergistic effect of the carbon nanotube catalytic coating with a catalyst inside, such as CNFs and Pt / CNTs. The protons generated by the reaction are transmitted to the other side through the proton exchange membrane, and the electrons generated by the reaction are collected by the bipolar plate and conducted to the external circuit to complete the conversion of electrical energy to chemical energy.
[0083] The liquid flow battery stack structure of this embodiment can effectively reduce the contact resistance between various materials, while reducing the volume and mass of the stack, thereby improving the overall power density of the liquid flow battery stack.
[0084] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the term "include", "comprise" or any other variant is intended to cover non-exclusive inclusion, so that the article or device including a series of elements includes not only those elements, but also other elements that are not explicitly listed. In the absence of more restrictions, the elements defined by the sentence "including one..." do not exclude the existence of other identical elements in the article or device including the elements. "Connect" or "connected" and similar words are not limited to physical or mechanical connections, but can include electrical connections, whether direct or indirect. The orientation or position relationship indicated by "up", "down", "left", "right", etc. is based on the orientation or position relationship shown in the accompanying drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention.
[0085] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A composite membrane-electrode for a flow battery, characterized in that: include: A proton exchange membrane coated with a catalytic coating and two liquid diffusion layers, wherein The proton exchange membrane comprises a Nafion membrane, and the proton exchange membrane comprises a main body and a plurality of synapse parts located on both sides of the main body; The multiple synaptic portions on each side are arranged in a parallel and equally spaced one-dimensional array along the main body, and the multiple synaptic portions on both sides are symmetrically arranged about the main body; The two liquid diffusion layers are correspondingly attached to a plurality of synapse portions on both sides of the proton exchange membrane.
2. The composite membrane-electrode for flow battery according to claim 1, characterized in that: The catalytic coating is a carbon nanotube catalytic coating with a catalyst loaded therein, and the catalyst is a metal-based catalyst, a metal oxide catalyst or a carbon-based electrocatalyst.
3. The composite membrane-electrode for flow battery according to claim 1, characterized in that: The distance between the main body and one end of the synapse part away from the main body is 0.1 μm to 100 μm.
4. The composite membrane-electrode for flow battery according to claim 1, characterized in that: The distance between adjacent synaptic parts is greater than 0.1 μm.
5. The composite membrane-electrode for flow battery according to claim 1, characterized in that: The liquid diffusion layer includes a carbon nanofiber layer.
6. A method for preparing a composite membrane-electrode for a flow battery, characterized in that: include: Step 1: Pour the Nafion solution into a template having a one-dimensional array structure, and evaporate the solvent to obtain a Nafion array membrane; Step 2: placing a strip Nafion membrane on a template having a Nafion array membrane, fusing the strip Nafion membrane with the Nafion array membrane by a hot pressing process, and obtaining a proton exchange membrane after demolding, wherein the strip Nafion membrane is located in the middle of the Nafion array membrane, so that the Nafion array membrane forms a plurality of synaptic portions on both sides of the strip Nafion membrane; Step 3: preparing a carbon nanotube material with a catalyst inside, and preparing a catalytic coating slurry using the carbon nanotube material with a catalyst inside; Step 4: spraying the catalytic coating slurry onto the entire surface of the proton exchange membrane to obtain a proton exchange membrane with a catalytic coating on the surface; Step 5: Prepare a liquid diffusion layer using carbon nanofibers; Step 6: Use a hot pressing process to bond two liquid diffusion layers to the multiple synapse parts on both sides of the proton exchange membrane to obtain a liquid flow battery composite membrane-electrode.
7. The method for preparing a composite membrane-electrode for a flow battery according to claim 6, characterized in that: The step 3 comprises: Step 3.1: Synthesizing carbon nanotube materials with catalysts loaded inside by wet impregnation method; Step 3.2: mixing the carbon nanotube material carrying the catalyst inside and the carbon nanofiber according to a certain proportion, wherein the mass fraction of the carbon nanotube material carrying the catalyst inside is 1 to 100 wt %, and the mass fraction of the carbon nanofiber is 0 to 99 wt %; Step 3.3: Disperse the mixture into a mixed solution of propanol and water containing Nafion solution, wherein the mass fraction of the Nafion solution is 1% to 10%, and the volume ratio of propanol to water is 1:1, and perform ultrasonic treatment on the mixed solution to form a uniformly dispersed suspension as a catalytic coating slurry.
8. The method for preparing a composite membrane-electrode for a flow battery according to claim 6, characterized in that: The step 5 comprises: Step 5.1: adding carbon nanofibers to a sodium dodecyl sulfate aqueous solvent containing a dispersant, and performing ultrasonic dispersion to obtain a uniformly dispersed suspension; wherein the mass ratio of the carbon nanofibers to the dispersant is 1:2; Step 5.2: After filtering and forming the suspension in step 5.1, remove the dispersant to obtain a carbon nanofiber layer as a liquid diffusion layer.
9. The method for preparing a composite membrane-electrode for a flow battery according to claim 6, characterized in that: In step 2 and step 6, the process parameters of the hot pressing process are: the hot pressing temperature is 120° C. to 170° C., and the hot pressing pressure is 1 to 10 MPa.
10. A liquid flow battery, characterized in that: It comprises the composite membrane-electrode for a liquid flow battery as described in any one of claims 1 to 5.